1988
DOI: 10.1002/jlb.44.6.500
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Murine Bronchoalveolar Macrophage Respiratory Burst: Comparison of Soluble and Particulate Stimuli

Abstract: Stimulation of the respiratory burst of murine bronchoalveolar macrophages obtained by lung lavage was studied using four different stimuli and different assay conditions. One soluble stimulus, phorbol myristate acetate (PMA), two intracellular particles, zymosan and Blastomyces dermatitidis conida, and one extracellular particle, B. dermatitidis yeast, were incubated with either freshly obtained macrophages in suspension or 2- and 48-hour macrophage monolayers. Suspension cultures were incubated with stimuli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The AM obtained at each BAL responded sharply to the stimulation with PMA. In this aspect, guinea pig AM are different than those of rabbit or mouse, which can be elicited by PMA only after a period of incubation with serum (12,31). Measurement of H2O2 production from guinea pig AM showed that these cells were very active in this respect (19).…”
Section: Discussionmentioning
confidence: 96%
“…The AM obtained at each BAL responded sharply to the stimulation with PMA. In this aspect, guinea pig AM are different than those of rabbit or mouse, which can be elicited by PMA only after a period of incubation with serum (12,31). Measurement of H2O2 production from guinea pig AM showed that these cells were very active in this respect (19).…”
Section: Discussionmentioning
confidence: 96%
“…Following contact with and/or ingestion of inhaled dusts, pulmonary phagocytes often display an increase in oxygen consumption with concomitant increase in production of superoxide anion (O 2 -), hydrogen peroxide (H 2 O 2 ), and other reactive oxygen intermediates. These events are commonly referred to as the "respiratory burst" (Housset & Junod, 1983;Kaku et al, 1983;Pabst & Johnston, 1980;Sugar & Field, 1988;Ward et al, 1986). Little is known concerning the possible role of phagocyte-derived oxygen radicals in the pathogenesis of pulmonary diseases due to organic dusts.…”
mentioning
confidence: 96%